Does government effectiveness moderate the relationship between regulatory quality and tax complexity? A tale of a hundred nations - Muhammad Dahlan (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2023)
This research aims to analyze the relationship between regulatory quality and tax complexity worldwide and whether this relationship is moderated by government effectiveness. The hypothesis is that robust regulations would promote simplicity and efficiency in the tax system. This study incorporates 100 countries as a sample, derived from the tax complexity index developed in 2016. Further, a moderated regression using SPSS PROCESS Macro is used to test the hypotheses and generate findings. This study shows that regulatory quality relates to the tax complexity in the countries and the effectiveness of the government indeed moderates this relationship. The tax authority, the Directorate General of Taxes, may use the findings to address the importance of the quality of regulations in shaping an efficient tax system.